Free- and peptide-based dietary arginine supplementation for the South American fish pacu (Piaractus mesopotamicus) - Tesser, M. B.; Terjesen, B. F.; Zhang, Y.; Portella, M. C.; Dabrowski, K. (Blackwell Publishing, 2005)
Arginine was hypothesized to be a model compound in the present study on molecular forms of indispensable amino acid (IAA) dietary supplementation. Juvenile South American pacu (Piaractus mesopotamicus) were fed diets containing arginine in a protein base (casein-wheat gluten or casein-gelatin), or the casein-wheat gluten base supplemented with dipeptide or free arginine at two levels (5 and 10 g kg(-1)). Growth and protein efficiency ratios were significantly affected by diets, but not by arginine molecular form. Three free dispensable amino acids (DAA) and four IAA in plasma were affected by diet, but plasma arginine concentrations did not differ. Plasma urea concentrations, being very low in the pacu, and hepatic arginase activities, were not affected by diet (P = 0.10-0.11), but together with plasma ornithine, mirrored the growth data. Molecular form of arginine supplementation, free or dipeptide, significantly changed several free IAA (Phe, Leu, Ile, His) and urea, with a higher mean plasma concentration in dipeptide fed fish. The dietary treatments, or molecular form of the arginine supplementation, did not change proximate composition, except that calcium levels decreased with higher dietary arginine supplementation level. The present study indicates that dipeptides can provide IAA to pacu, and that arginine supplemented in this form is utilized as efficiently as in free form.
Keywords: arginine; dipeptide; free amino acids; pacu; Piaractus mesopotamicus; urea